TGF-β1 Sensitizes TRPV1 through Cdk5 Signaling in Odontoblast-Like Cells. (13th May 2013) - Utreras, Elias; Prochazkova, Michaela; Terse, Anita; Gross, Jacklyn; Keller, Jason; Iadarola, Michael J; Kulkarni, Ashok B
Background: Odontoblasts are specialized cells that form dentin and they are believed to be sensors for tooth pain. Transforming growth factor-β1 (TGF-β1), a pro-inflammatory cytokine expressed early in odontoblasts, plays an important role in the immune response during tooth inflammation and infection. TGF-β1 is also known to participate in pain signaling by regulating cyclin-dependent kinase 5 (Cdk5) in nociceptive neurons of the trigeminal and dorsal root ganglia. However, the precise role of TGF-β1 in tooth pain signaling is not well characterized. The aim of our present study was to determine whether or not in odontoblasts Cdk5 is functionally active, if it is regulated by TGF-β1, and if it affects the downstream pain receptor, transient receptor potential vanilloid-1 (TRPV1). Results: We first determined that Cdk5 and p35 are indeed expressed in an odontoblast-enriched primary preparation from murine teeth. For the subsequent analysis, we used an odontoblast-like cell line (MDPC-23) and found that Cdk5 is functionally active in these cells and its kinase activity is upregulated during cell differentiation. We found that TGF-β1 treatment potentiated Cdk5 kinase activity in undifferentiated MDPC-23 cells. SB431542, a specific inhibitor of TGF-β1 receptor 1 (Tgfbr1), when co-administered with TGF-β1, blocked the induction of Cdk5 activity. TGF-β1 treatment also activated the ERK1/2 signaling pathway, causing an increase in early growth response-1 (Egr-1), a transcription factor that induces p35 expression. In MDPC-23 cells transfected with TRPV1, Cdk5-mediated phosphorylation of TRPV1 at threonine-407 was significantly increased after TGF-β1 treatment. In contrast, SB431542 co-treatment blocked TRPV1 phosphorylation. Moreover, TGF-β1 treatment enhanced both proton- and capsaicin-induced Ca 2+ influx in TRPV1-expressing MDPC-23 cells, while co-treatment with either SB431542 or roscovitine blocked this effect. Conclusions: Cdk5 and p35 are expressed in a murine odontoblast-enriched primary preparation of cells from teeth. Cdk5 is also functionally active in odontoblast-like MDPC-23 cells. TGF-β1 sensitizes TRPV1 through Cdk5 signaling in MDPC-23 cells, suggesting the direct involvement of odontoblasts and Cdk5 in dental nociceptive pain transduction.